The Influence of the Level of Public Knowledge on the Rationality of Self-Medicine for Diarrhea in Sukaratu Tasikmalaya - Arman, Siti Alisa; Wahlanto, Panji (LPPM STIKes Muhammadiyah Ciamis, 2024)
Self-medication is one of the choices of Indonesian people in treating their illnesses, one of which is treating diarrhea. Diarrhea is a symptom of abnormality in frequent bowel movements, with liquid stool consistency. The frequency of bowel movements is said to be abnormal if it is more than three times a day. The purpose of this study was to determine the relationship between the level of knowledge and the rationality of self-medication for diarrhea in Sukaratu Tasikmalaya. This study is an observational study, with a research design with a cross-sectional approach. The number of research samples was 43 people from Batu Bulu Village, Linggajati Village, Sukaratu District, Tasikmalaya Regency. The sampling technique was carried out using purposive sampling. Research data were obtained from questionnaires. Analysis of research data using the Pearson Correlation test, to determine the relationship between the level of community knowledge and the rationality of self-medication for diarrhea. The results showed that out of 43 respondents, 36 respondents had a level of knowledge in the good category, 2 respondents were sufficient and 5 respondents had poor knowledge. The distribution of rationality for self-medication for diarrhea showed that 24 respondents had the right rationality and 19 respondents had the wrong rationality.